Pengembangan Aplikasi Digital UMKM Berbasis Hybrid Development dengan React Native dan Supabase Menggunakan Metode R&D - Wisudawan, Ilham; Widiono, Suyud (Jurnal Informatika Universitas Pamulang, 2025)
Digital transformation has become a key element in enhancing the competitiveness and operational efficiency of Micro, Small, and Medium Enterprises (MSMEs). However, many MSME actors in Sleman, particularly in Minggir District, still face challenges in digitalization, such as low digital literacy, limited motivation and managerial capabilities, uneven network quality, and insufficient organizational readiness. This study aims to develop a digital MSME application based on hybrid development using React Native and Supabase as an efficient and affordable cross-platform solution. The research employed a Research and Development (R&D) method following five main stages: needs analysis, system design, implementation, testing, and evaluation. Testing of the core features—including user authentication, product management, sales transactions, and financial reporting—was conducted through 25 Black Box test cases, achieving a success rate of over 95%. Usability evaluation using the System Usability Scale (SUS) involved 50 MSME respondents, selected through purposive sampling based on business type diversity and digital experience, resulting in an average score of 84.2 (Excellent category), indicating that the application is user-friendly, efficient, and aligned with MSME operational needs. This study provides a practical contribution in the form of a prototype application that supports the digitalization process of MSMEs and a theoretical contribution to the literature on hybrid development based on Backend-as-a-Service (BaaS). The implementation results demonstrate the system’s effectiveness within the Minggir District, Sleman, with potential generalizability for application in other regions with similar conditions and MSME characteristics.